2006
DOI: 10.1177/0192636506288858
|View full text |Cite
|
Sign up to set email alerts
|

Principals' Knowledge of Fundamental and Current Issues in Special Education

Abstract: The purpose of the study is to determine the comprehensive knowledge base of national secondary principals related to special education issues. Using a survey developed from the empirical and conceptual literature for assessing fundamental and current issues in special education, data were collected from a national sample of secondary school principals. Overall, principals report being well informed in fundamental issues. Although the relationship between demographics and knowledge produced mixed results, prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 33 publications
6
58
0
Order By: Relevance
“…To be competent administrators, principals should have a fundamental knowledge of special education as well as knowledge of current issues in special education (Wakeman et al, 2006). The need for professional development on special education topics for principals in the public school arena has been well established (Collins & White, 2001;DiPaola & Walther-Thomas, 2003;Goor, Schwenn, & Boyer, 1997;Lasky & Karge, 1995;Monteith, 2000;Sage & Burrello, 1994;Smith & Colon, 1998;Strahan, 1999;Valente, 2001;Valesky and Hirth, 1992).…”
Section: Literature Review Principals and Attitudes Toward Serving Stmentioning
confidence: 99%
See 1 more Smart Citation
“…To be competent administrators, principals should have a fundamental knowledge of special education as well as knowledge of current issues in special education (Wakeman et al, 2006). The need for professional development on special education topics for principals in the public school arena has been well established (Collins & White, 2001;DiPaola & Walther-Thomas, 2003;Goor, Schwenn, & Boyer, 1997;Lasky & Karge, 1995;Monteith, 2000;Sage & Burrello, 1994;Smith & Colon, 1998;Strahan, 1999;Valente, 2001;Valesky and Hirth, 1992).…”
Section: Literature Review Principals and Attitudes Toward Serving Stmentioning
confidence: 99%
“…The need for professional development on special education topics for principals in the public school arena has been well established (Collins & White, 2001;DiPaola & Walther-Thomas, 2003;Goor, Schwenn, & Boyer, 1997;Lasky & Karge, 1995;Monteith, 2000;Sage & Burrello, 1994;Smith & Colon, 1998;Strahan, 1999;Valente, 2001;Valesky and Hirth, 1992). However, as Wakeman et al (2006) suggested, there is little actual professional development in special education provided for public school principals. In addition to knowledge of special education, Ramirez (2006) suggested that the principal-as the instructional leader and agent of change-must posses other competencies, such as, "skills in effective instruction, assessment and discipline to provide support and feedback to teachers as they develop environments for teaching heterogeneous groups of students" (p. 63).…”
Section: Literature Review Principals and Attitudes Toward Serving Stmentioning
confidence: 99%
“…As a result, researchers have conducted a small number of survey studies examining principals' knowledge and beliefs of inclusion, knowledge of special education law, and comprehensive knowledge of current special education issues and found that overall, many elementary principals are undecided about the benefits of implementing inclusive practices (Barnett & Monda-Amaya, 1998;Guzman, 1996;Praisner, 2003;Villa, Thousand, Meyers, & Nevin, 1996), have limited knowledge of effective instruction for students with disabilities (Wakeman, Browder, Flowers, & Ahigrim-Delzell, 2006), fair knowledge of comprehensive special education issues, and moderate knowledge of special education legal procedures (Davidson & Algozzine, 2002;Davidson & Gooden, 2001). However, Wakeman et al (2006) found that middle school principals who reported higher levels of special education knowledge were more involved in special education instructional programs. Furthermore, research indicates the majority of principals feel poorly prepared for jobs as special education leaders (Bateman & Bateman, 2002;Crockett, 2002b;DiPaola & Walther-Thomas, 2003;Monteith, 2000) and report that their administrative preparation programs did not adequately prepare them to support teachers who instruct students with disabilities (DiPaola & Walther-Thomas, 2003;Lasky & Karge, 2006).…”
Section: Principal Leadership and Special Educationmentioning
confidence: 92%
“…The principal's role is imperative in implementing change in schools (DiPaola & Walther-Thomas, 2003;Fullen, 2001;Gardiner & Enomoto, 2006;Monteith, 2000). The position of the school site principal has transformed from a building manager to the instructional leader (DiPaola & Walther-Thomas, 2003;Grogan & Andrews, 2002;Shellard, 2003;Wakerman, Browder, Flowers & Ahlgrim-Delzell, 2006). In order for any innovative program to be successfully implemented in a school, the school site principal must have the fundamental knowledge to lead that change (Wakerman et al, 2006).…”
Section: Purpose Of the Studymentioning
confidence: 99%
“…The position of the school site principal has transformed from a building manager to the instructional leader (DiPaola & Walther-Thomas, 2003;Grogan & Andrews, 2002;Shellard, 2003;Wakerman, Browder, Flowers & Ahlgrim-Delzell, 2006). In order for any innovative program to be successfully implemented in a school, the school site principal must have the fundamental knowledge to lead that change (Wakerman et al, 2006). In the case of inclusion, this fundamental knowledge is in the area of special education.…”
Section: Purpose Of the Studymentioning
confidence: 99%